Prevalencia de depresión como estado o como rasgo según el género en pacientes con insuficiencia renal crónica que reciben tratamiento de hemodiálisis en el Hospital General Isidro Ayora Loja - Figueroa Salazar, Diana Stefanía (2018)
Patients with chronic renal failure can present depression as a state or as a trait like a answer to the illness, this investigation: “Prevalence of depression as a state or as a trait according to gender in patients with chronic renal failure who receives hemodialysis treatment at Isidro Ayora Loja´s General Hospital”, has as general objetive, describe the prevalence of depression as a state or as a trait according to gender; this is a exploratory, descriptive, quantitative, non-experimental study, the sample of the study was conformed by 50 patients. It has been used IDERE inventory in order to measure out depression as a state or as a trait, it was rated in base of three indicators (high, medium,and low) to state and trait respectively, according to results of high category that are the most significants, it has been showed, that the major porpotion of the population in the study has higher scores at depression as a state, and lower scores at depression as a trait, also the prevalence is higher in femenine gender according to depression as a state or as a trait , and it has been identified major proportion of depression as a state or as a trait at age range major of 52 years. Finally, I recommend to aply the psychological intervention that searchs the wellness of patients Key words: depressive-symptoms-fixed-reactive-dialysis